Pengaruh Konsumsi Jambu Biji Merah Dan Madu Sari Kurma Terhadap Jumlah Trombosit Pasien Anak Dengan DHF Di RS Bhakti Asih Brebes - Azizun Hakimah, Nurul; Nopi Nur Khasanah; Kurnia Wijayanti (STIKes Ibnu Sina Ajibarang, 2025)
Dengue Hemorrhagic Fever (DHF) increases the permeability of capillary walls, impacting the decrease in plasma volume and consequently reducing the platelet count. Consumption of red guava and date palm honey can increase platelets in DHF patients. This study aimed to determine the effect of red guava and date palm honey consumption on platelet count in children with DHF. This quasi-experimental study used a non-equivalent parallel group design. A total of 30 DHF patients at RS Bhakti Asih Brebes were selected using purposive sampling technique and divided into three groups: group A (red guava juice), group B (date palm honey), and group C (red guava juice and date palm honey). Platelet counts were obtained from laboratory results. Analysis was performed using the Anova test for normally and heterogeneously distributed data. Post hoc tests were conducted to determine the most effective treatment among the three groups. There was a significant difference in the mean platelet count before and after treatment in group A (-11.6±12.204; p = 0.015), group B (-16.2±16.033; p = 0.011), and group C (-27.5±22.741; p = 0.004). There was a significant difference between the three treatment groups on platelet count in children with DHF (p = 0.045). Date palm honey administration had the best effectiveness in increasing the mean platelet count compared to other groups. Pre-clinical testing-based research needs to be considered to determine the more accurate effect of the combination of red guava juice and date palm honey.